A brief review of variable stiffness and damping magnetorheological fluid dampers - Deng, Huaxia; Lian, Xinyu; Gong, Xinglong (Frontiers in Materials, 2022)
With the development of magnetorheological fluid (MRF) technology, variable stiffness and damping MRF dampers as semi-active controllers gradually show their unique advantages in the vibration control field. This paper reviews recent journal articles on the principles, characteristics, structure design, modelling and applications of variable stiffness and damping MRF dampers. The principle includes the force behaviour of the MRF fluid and the mechanism of the variable stiffness and damping MRF damper. Characteristics introduce the damper's force-displacement relationships, which have frequency dependence and amplitude dependence. Following this, typical dampers structures are discussed, including electromagnetic design and coil configuration. After that, some common models and parameter optimization methods are presented. Furthermore, taking vehicle suspension as an example, the applications of variable stiffness and damping MRF dampers in some fields are proposed in this paper.